Protective effects of a recombinant fragment of human surfactant protein D in a murine model of pulmonary hypersensitivity induced by dust mite allergens. - Singh, M; Madan, T; Waters, P; Parida, S; Sarma, P; Kishore, U (2003)
Lung surfactant protein D (SP-D) is a carbohydrate pattern recognition immune molecule. It can interact with a range of pathogens, stimulate immune cells and manipulate cytokine profiles during host's immune response. SP-D has also been shown to interact, via its carbohydrate recognition domains, with glycoprotein allergens of house dust mite (Dermatophagoides pteronyssinus, Derp), inhibiting specific IgE isolated from mite-sensitive asthmatic patients from binding these allergens, and blocking subsequent histamine release from sensitized basophils. In the present study, we have examined the protection offered by various doses of intranasal administration of a recombinant fragment of human SP-D (rhSP-D) in a murine model of pulmonary hypersensitivity to Derp allergens which showed characteristic high levels of specific IgE antibodies, peripheral blood eosinophilia, pulmonary infiltrates and a Th2 cytokine response. Treatment of Derp mice with rhSP-D led to significant reduction in Derp-specific IgE levels, blood eosinophilia and pulmonary cellular infiltration. The levels of IL-4 and IL-5 were decreased, while those of IL-12 and IFN-gamma were raised in the supernatant of the cultured splenocytes, indicating a Th2 to Th1 polarization. These results suggest that SP-D has a protective role in the modulation of allergic sensitization and in the development of allergic reactions to Derp allergens and highlight potential of the rhSP-D as a therapeutic for pulmonary hypersensitivity.